Roles of cholesterol in vesicle fusion and motion - Zhang, Jing (2012)
Although it is well established that exocytosis of neurotransmitters and hormones is highly regulated by numerous secretory proteins, such as SNARE proteins, there is an increasing appreciation of the importance of the chemophysical properties and organization of membrane lipids to various aspects of the exocytotic program. Based on amperometric recordings by